2019
DOI: 10.1002/lpor.201800256
|View full text |Cite
|
Sign up to set email alerts
|

Carrier‐Envelope‐Offset Frequency Stable 100 W‐Level Femtosecond Thin‐Disk Oscillator

Abstract: In this paper, the carrier‐envelope‐offset (CEO) frequency stabilization of a Kerr‐lens mode‐locked femtosecond oscillator with average power 105 W is presented. Intra‐cavity Kerr lensing is realized in a quartz crystal that simultaneously serves as an acousto‐optic loss modulator. This novel method results in a CEO frequency stable laser with high average power and a residual in‐loop phase noise below 90 mrad. Furthermore, an all‐solid‐state bulk broadening stage is presented. The compressed, CEO frequency‐st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Similar peaks can also be observed in the stabilized CEO signal in Ref. [16], and although harmonics are barely distinguishable in the results reported in [3], [15], there is a pronounced contribution to the integrated phase noise at ∼7 kHz. We did not investigate the origin of these noise peaks, however it was previously suggested that they might arise from the power supply of the pump diode, as they are clearly visible in its relative intensity noise [11].…”
Section: Free-running Noise and Locked Performancesupporting
confidence: 83%
See 3 more Smart Citations
“…Similar peaks can also be observed in the stabilized CEO signal in Ref. [16], and although harmonics are barely distinguishable in the results reported in [3], [15], there is a pronounced contribution to the integrated phase noise at ∼7 kHz. We did not investigate the origin of these noise peaks, however it was previously suggested that they might arise from the power supply of the pump diode, as they are clearly visible in its relative intensity noise [11].…”
Section: Free-running Noise and Locked Performancesupporting
confidence: 83%
“…Another demonstrated method for CEO stabilization of TDLs employs an acousto-optic modulator (AOM) in the oscillator [3], [16] enabling a direct modulation of the intracavity losses. This scheme proved to be power-scalable and allowed the realization of a tight CEO lock due to a large locking bandwidth of 230 kHz.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel to these efforts, large progress has been made in finding paths for efficient external pulse compression of these high-average power laser systems using hollow-core fibers [48], multi-pass cells [49][50][51][52], hybrid setups including multi-plate compressors [53], and even spectral broadening in the amplifier itself [54] bringing these applications one step closer. Additionally, as the pulse durations from these systems keeps getting shorter and approach the few-cycle regime, carrier-envelope phase control becomes increasingly relevant, in particular for high-power oscillators which can be used as powerful seeds for booster amplifiers [55,56].…”
Section: Resultsmentioning
confidence: 99%